PENGARUH PERBEDAAN BENTUK DAN WARNA UMPAN BUATAN TERHADAP HASIL TANGKAPAN GURITA DI PERAIRAN SIMEULUE - Roy Amonda; T. Faizul Anhar; Faisal Syahputra (JURNAL KREASI RAKYAT, 2025)
Simeulue Regency is one of the island regions located in Aceh Province, situated in the Indian Ocean, and is endowed with abundant fishery resources. One of the economically valuable commodities in this area is octopus (Octopus). Local fishermen commonly use artificial bait shaped like crab shells and cake molds, in red, orange, and yellow colors. This study aims to determine the effect of differences in the shape and color of artificial bait on octopus catch rates in the waters of Simeulue. The method used was experimental fishing with a Randomized Block Design (RBD). The results of ANOVA analysis showed that both bait shape and color had a significant effect on octopus catch rates, with F-values of 14.950 for shape and 23.708 for color. The crab shell-shaped bait resulted in higher catch yields compared to the cake mold-shaped bait, and orange was the most effective color among the three. A total of 91 octopuses were caught, with 52 caught using crab shell-shaped bait and 39 with cake mold-shaped bait. These findings suggest that using orange-colored, crab shell-shaped artificial bait can enhance the effectiveness of octopus fishing.